Manual Scaling of Ionograms Measured at Jeju (33.4°N, 126.3°E) - Yong Ha Kim; Ki-nam Kim (Journal of Astronomy and Space Sciences, 2018)
The ionosphere has been monitored by ionosondes for over five decades since the 1960s in Korea. An ionosonde typically produces an ionogram that displays radio echoes in the frequency-range plane. The trace of echoes in the plane can be read either manually or automatically to derive useful ionospheric parameters such as foF2 (peak frequency of the F2 layer) and hmF2 (peak height of the F2 layer). Monitoring of the ionosphere should be routinely performed in a given time cadence, and thus, automatic scaling of an ionogram is generally executed to obtain ionospheric parameters. However, an auto-scaling program can generate undesirable results that significantly misrepresent the ionosphere. In order to verify the degree of misrepresentation by an auto-scaling program, we performed manual scaling of all 35,136 ionograms measured at Jeju (33.43˚N, 126.30˚E) throughout 2012. We compared our manually scaled parameters (foF2 and hmF2) with auto-scaled parameters that were obtained via the ARTIST5002 program. We classified five cases in terms of the erroneous scaling performed by the program. The results of the comparison indicate that the average differences with respect to foF2 and hmF2 between the two methods approximately correspond to 0.03 MHz and 4.1 km, respectively with corresponding standard deviations of 0.12 MHz and 9.58 km. Overall, 36 % of the auto-scaled results differ from the manually scaled results by the first decimal number. Therefore, future studies should be aware of the quality of auto-scaled parameters obtained via ARTIST5002. Hence, the results of the study recommend the use of manually scaled parameters (if available) for any serious applications.